Analisis Swot Terhadap Tantangan Dan Peluang Periode Tahun 2023 Serta Strategi Dalam Sustainable Business Bank Muamalat Indonesia - Mochammad Saichu Abdullah Busaeri; Zainal Arif (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2025)
Sharia banking as the first sharia economic financial institution in Indonesia has only started since the first sharia bank was established, namely Bank Muamalat Indonesia. The objectives of this study are: To analyze the challenges and opportunities faced for the 2023 period and analyze the strategy in sustainable business of Bank Muamalat Indonesia, as the first sharia bank in Indonesia. This research is a qualitative descriptive type with a case study approach (Case Study). This data source comes from the company's management consisting of of Bank Muamalat Indonesia. The analysis method used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Based on the research results, it can be concluded that : (1) The challenges and opportunities faced by Bank Muamalat Indonesia in its development and its relation with Islamic Banking Law in Indonesia its suistainable business efforts consist of the existence of Laws and Government Regulations concerning Islamic banking which are continuously updated and the growing Islamic economy in Indonesia. Meanwhile, the challenges or threats faced by Bank Muamalat Indonesia include the challenges of global economic uncertainty and geopolitical conditions which are still less conducive, (2) Bank Muamalat's strategy to survive and develop is that Bank Muamalat Indonesia has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be implemented in this condition is to support an aggressive growth policy. This study is different from previous studies in that this study analyzes strategies in sustainable Bank Muamalat Indonesia. Keyword : Sharia Banking, Challenges, Opportunities, Strategies, Sustainable Business